Microcomputed tomography analysis of curved root canal preparation when coronal flaring and glide path files used with heat-treated nickel titanium rotary files. - Ammar AbuMostafa; Mohammed M Alrefaie; Nedal Abu-Mostafa; Fahda N Algahtani (PLoS ONE)
The objective was to evaluate the effect of glide path and coronal flaring on the dentin volume removal and percentage of touched walls in curved canals using two heat-treated rotary files. The mesiobuccal canal of forty-eight, randomly selected, extracted mandibular molars was divided into two groups of 24 each, according to the type of instrument used (RACE EVO and EdgeSequel rotary files). Each group was further divided into three subgroups; Group (A): Control using one file shaped to 04/30, Group (B) with a glide path (EdgeGlidePath (EGP)), and Group (C): with a glide path and coronal flaring (EGP and EdgeTaper Platinum (ETP) SX file respectively). The root canals were then instrumented using the assigned instruments. The assessment was carried out using micro-CT. The comparison of the mean values of the tested groups about dentin volume removal and percentage of untouched walls did not reach statistical significance (p<0.05). Glide path and coronal flaring had an insignificant effect on the dentin volume removal and percentage of untouched walls in curved canals.